O sujeito neoliberal mirim: a semântica da obediência retratada em vídeos de YouTube - Calonego, Mariana (2023)
Considering childhood as a product of culture, his understanding requires the comprehension of social organization modes. Under the globalized logic of capitalism, subjectivities embody the neoliberal logic of performance and competitiveness. Adding technological dominance in people's daily lives, ways of working, relationships and desire undergo important transformations in contemporary times. In face of this, childhood suffers the consequences. Being assigned to children’s the role of corresponding to an overqualified place, they are expected to become, ever earlier, ready for future participation in a competitive labor market. “Already being” becomes the imperative of this moment. Access to digitality, fosters this logic and allows for a type of social participation that goes in the direction of “already being” a professional: young youtuber. In this research, we used the YouTube video platform to investigate the role of children nowadays. Based on Discourse Analysis, we analyzed videos starring children’s and identified aspects that put them in similar conditions to those of the neoliberal subject. The results of the data analysis, indicate a professionalization of the channels that, together with the present narratives in the videos, enunciate a neoliberal discourse. In addition, the dedication of the channels to a supposed transmission of conduct parameters to children, engenders the idea of a semantics of obedience, which seems to translate what is socially expected from children.